Answer:
0=2
There are no solutions
Step-by-step explanation:
Answer:
7
Step-by-step explanation:
7-4=3
5×3=15
plz mark brainliest
The value is 333
<h3>How to determine the function</h3>
From the information given, we have:
- x = - 8
- 1/3*h(x) = x^2-5x+7
Now, let's substitute the value of 'x' in the function:
1/3*h(x) = x^2-5x+7
1/ 3 × h(-8) = ( - 8)² - 5 ( -8) + 7
Make 'h ( -8)' the subject of formula
h ( -8) = 
h ( -8) = 
Take the sum of the numerator
h ( -8) = 
Take the inverse of the denominator and multiply
h ( -8) = 111 × 3/ 1
h ( -8) = 333
We can see that through the substitute of the value of x as - 8, we get 333
Thus, the value is 333
Learn more about algebraic expressions here:
brainly.com/question/723406
#SPJ1
Answer:
The "power rule" tells us that to raise a power to a power, just multiply the exponents. Here you see that 52 raised to the 3rd power is equal to 56.
Step-by-step explanation:
The complete question in the attached figure
we have that
f(x) = x²<span> + 1
g(x) = x – 4
step 1
find </span>(f o g)(x)
(f o g)(x)= (x - 4)² + 1(f o g)(x) = x² - 8x + 16 + 1
(f o g)(x) = x² - 8x + 17
step 2
find (f o g)(10)
(f o g)(10) = 10² - 8*(10) + 17
(f o g)(10 = 100 - 80 + 17
(f o g)(10)= 37
the answer is 37